Surface Preparation Techniques for Adhesive Bonding. - Wegman, Raymond F. (Elsevier Science, 2012)
Surface Preparation Techniques for Adhesive Bonding is an essential guide for materials scientists, mechanical engineers, plastics engineers, scientists and researchers in manufacturing environments making use of adhesives technology. Wegman and van Twisk provide practical coverage of a topic that receives only cursory treatment in more general books on adhesives, making this book essential reading for adhesion specialists, plastics engineers, and a wide range of engineers and scientists working in sectors where adhesion is an important technology, e.g. a.
3.3 Preparation of Titanium by the Turco 5578 Process.
Keywords: Adhesives.; Surface preparation.; elektronické knihy; electronic books